Depressive symptoms, drinking patterns and farm-work injury among Colorado farm residents - Leff, Marilyn Grace Petersen, author; Stallones, Lorann, advisor (Colorado State University. Libraries, 2008)
Introduction. Farm-work injury is a major occupational health problem. The purposes of this study were to (1) describe farm residents who are heavy drinkers with high depressive symptoms and (2) assess the association between farm-work injury and depressive symptoms, farm-work injury and drinking pattern, and farm-work injury and the interaction of these two in cross-sectional and prospective analysis. Methods. A population-based sample of farm residents within Colorado was followed for three years. Information on socio-demographic and health related variables were gathered including farm-work injuries, depressive symptoms, and alcohol use. Multinomial logistic regression was used to describe differences and similarities between farm residents with high depressive symptoms and heavy drinking, high depressive symptoms only, and heavy drinking only compared to those without either. Poisson regression with repeated measures was conducted to estimate the effect of depressive symptoms and alcohol use and the interaction between the two variables on farm-work injury. Results. An association between smoking and co-occurring heavy drinking and high depressive symptoms was found (OR 3.69, 95% CI 1.0, 13.1) that was not seen among those with heavy drinking only or high depressive symptoms only. Time spent in farm work was also associated with depressive symptoms and with co-occurring heavy alcohol use. In both the cross-sectional and prospective regression analyses, no association was found between drinking pattern and injury for men or for women. After adjusting for age and smoking status, high depressive symptoms was associated with farm-work injuries among women (OR 3.6, 95% CI 1.8-6.9) in the cross-sectional analysis but not in the prospective analysis. No association between farm-work injuries and depressive symptoms was found for men. No interaction between drinking pattern and depressive symptoms in relation to injuries was seen in either men or women. Discussion/Conclusions. The association between smoking and co-occurrence of heavy drinking and high depressive symptoms may provide useful information for smoking cessation efforts. Depressive symptoms were more likely a result of farm-work injury in women rather than a cause. Future studies are needed to understand the impact of farm-work injuries in the context of differences in the roles of men and women farmers.
Keywords: Colorado; depression; drinking patterns; farm residents; farm-work injury; clinical psychology; epidemiology